THE USE OF 2% CHLORHEXIDINE GLUCONATE (CHG) AS A DAILY BATHING TO REDUCE BACTEREMIA IN CHILDREN WITH CRITICAL ILLNESS AT PICU/NICU - Nopi Nur Khasanah (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2016)
Background: Bacteremia frequently occurs because of nosocomial infection that actually could be preventable. In children who are hospitalized ussually have a higher risk to experience it. Especially in children with critical illness at Pediatric Intensive Care Unit (PICU) at which the state of children to get an indication of central venous catheters (CVC). Objective: To analyze the use of 2% Chlorhexidine Gluconate (CHG) as a daily bathing treatment to reduce bacteremia in critically ill children in the PICU/NICU. Discussion: The study of the use 2% CHG as a daily bathing treatment for critically ill patients admitted to the intensive care unit has been carried out. However, only performed in adult patients. Developing research conducted in children, this study recommends the use of 2% CHG as a daily bathing treatment can be used in selected patients in the NICU when there is an effort by other measures, but still failed to reduce the incidence of CLABSI. Conclusions: Implementation of recommendations will involve approval by the appropriate organizational structure in charge of monitoring the evolution of the practice. Need staff whom known the instructions on the use of CHG to develop procedures daily bathing with 2% CHG in intensive care and decrease the incidence of bacteremia,.Keywords: Chlorhexidine Gluconate, Daily Bathing, Bacteremia in children, PICU/NICU.